Evaluation of operational parameters for clinical evaluation of skin hydration by corneometry method - Laura Moretti Aiello; Mariane Massufero Vergílio; Silas Arandas Monteiro e Silva; Gislaine Ricci Leonardi (Brazilian Journal of Pharmaceutical Sciences)
Abstract The Corneometer CM® 825 from Courage & Khazaka electronic GmbH is widely utilized in clinical efficacy testing of cosmetics. Assessing methodological variables is crucial for ensuring the reliability of the process. The aim of this study was to evaluate the operational and instrumental parameters of the Corneometer CM® 825 in the clinical assessment of skin hydration levels. Precision and accuracy of the measurements were assessed by measuring hydration levels on 10 participants in specific areas of the forearm and face. Three different skin conditions (dry, normal, and hydrated) resulting from the use or non-use of moisturizing cosmetics and a drying promoter were evaluated within 120 minutes of their application. The electrical capacitance method demonstrated good repeatability, with coefficients of variation mostly below 10%. However, higher variability was observed in inter-observer readings. The equipment exhibited high sensitivity and accurately discriminated the differences between hydrated and dry skin. Operational training and standardization of the methodology are essential to ensure accurate, reproducible, and reliable results in studies utilizing the Corneometer equipment for assessing skin hydration levels.